2019
DOI: 10.1186/s13048-019-0567-4
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C inhibits apoptosis of porcine primary granulosa cells cultured in vitro

Abstract: Phospholipase C (PLC) can participate in cell proliferation, differentiation and aging. However, whether it has a function in apoptosis in porcine primary granulosa cells is largely uncertain. The objective of this study was to examine the effects of PLC on apoptosis of porcine primary granulosa cells cultured in vitro. The mRNA expression of BAK, BAX and CASP3, were upregulated in the cells treated with U73122 (the PLC inhibitor). The abundance of BCL2 mRNA, was upregulated, while BAX and CASP3 mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Apoptosis of GCs leads to follicular atresia . Studies have shown that estrogen (E2) concentration was higher in healthy follicles, while progesterone (P4) and testosterone (T) concentrations were higher in atretic follicles. , Thus, the proliferation, apoptosis, and steroidogenesis of GCs are important for follicular development and atresia.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis of GCs leads to follicular atresia . Studies have shown that estrogen (E2) concentration was higher in healthy follicles, while progesterone (P4) and testosterone (T) concentrations were higher in atretic follicles. , Thus, the proliferation, apoptosis, and steroidogenesis of GCs are important for follicular development and atresia.…”
Section: Introductionmentioning
confidence: 99%
“…Thought to be key transcription factors for immune cell activation and differentiation, NFAT family members were also suggested to be involved in adipocyte differentiation, modulation of adipokine gene expression, and to participate in glucose and insulin homeostasis [ 105 , 107 109 ]. Although NFATC1 was upregulated following stimulation of porcine granulosa cells with a phospholipase C (PLC) activator [ 110 ], the actions mediated by the NFAT family in granulosa cells still remain poorly understood. Functional classification of the 38 downstream effector genes of the NFAT canonical pathway using PANTHER Classification systems showed that the differentially expressed genes were, among others, related to inflammation mediated by chemokine and cytokine signaling pathways, and to the 5HT2 type receptor or serotonin receptor (5-HT2A) signaling pathway which is known to stimulate an increase in intracellular Ca 2+ levels via the PLC/IP3/DAG pathway [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that isorhamnetin restores GCs proliferation against ZEA-induced apoptosis and subsequently increases the S phase of DNA synthesis via the PI3K/Akt. Healthy follicles have higher concentrations of E2 [14,36]. Thus, the steroidogenesis of GCs is essential for atresia and follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…GCs were mixed in DMEM/F12 medium supplemented with1% streptomycin-penicillin and 8% fetal bovine serum (FBS) (Serapro, Germany). GCs were cultured at 37°C in 5% CO2 for 36 to 44 h. After, GCs were cultured with isorhamnetin and ZEA, and incubated for 24 h in DMEM/F12 medium containing transferrin (2.5 mg/mL), 0.5% bovine serum albumin (BSA) (w/v), sodium bicarbonate (10 mM), insulin (50 ng/mL), sodium selenite (5 ng/mL), FSH (0.1 IU/mL), penicillin (100 U/mL), streptomycin (100 mg/mL) and nonessential amino acid mix (1×) [14]. GCs were collected for protein and mRNA extraction.…”
Section: Culture and Treatment Of Gcsmentioning
confidence: 99%